2018
DOI: 10.1111/ajag.12589
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary behaviour in a residential aged care facility

Abstract: ObjectiveTo evaluate sedentary behaviour and physical activity levels in independently mobile older adults with and without dementia living in residential aged care.MethodsSedentary behaviour and physical activity were measured in 37 residents of an aged care facility using an accelerometer worn during waking hours for five days.ResultsParticipants with valid accelerometer data (n = 28) spent 85% of the time sedentary, and 12% in low‐intensity, 2% in light‐intensity and 1% in moderate‐to‐vigorous‐intensity phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 27 publications
2
46
2
Order By: Relevance
“…Our nursing home residents spent, on average, more than two and a half hours sitting or lying down without interruptions (21.5% of their waking time) and more than nine hours, or 77.2%, of their waking time sedentary. These findings are similar to or even higher than results of other studies, which examined sedentary behavior under free living conditions in older adults (74.5%, 65%, and 66% of wear time) [ 59 , 63 , 64 ], and also similar to or a bit lower than studies which examined sedentary behavior of nursing home residents (79% and 85% of wear time) [ 18 , 65 ]. The small discrepancies might be due to differences in (1) facility-organized activities, (2) regional differences of the examined nursing homes, (3) physical limitations of the residents, or (4) the devices that the activity was measured with.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our nursing home residents spent, on average, more than two and a half hours sitting or lying down without interruptions (21.5% of their waking time) and more than nine hours, or 77.2%, of their waking time sedentary. These findings are similar to or even higher than results of other studies, which examined sedentary behavior under free living conditions in older adults (74.5%, 65%, and 66% of wear time) [ 59 , 63 , 64 ], and also similar to or a bit lower than studies which examined sedentary behavior of nursing home residents (79% and 85% of wear time) [ 18 , 65 ]. The small discrepancies might be due to differences in (1) facility-organized activities, (2) regional differences of the examined nursing homes, (3) physical limitations of the residents, or (4) the devices that the activity was measured with.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, a few studies examined PA patterns in ambulatory or long-term care settings, and if so, only for a short period of time. Research showed that persons in need of care spend more than 80% of their waking time lying down or sitting [ 17 , 18 , 19 ]. Buckinx and colleagues revealed that this population walks, on average, less than 1700 steps per day [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the blood glucose levels in the control group were significantly higher than those in the experimental group after the intervention. In related studies [8,10,[17][18][19][20], older adults that participated in a physical activity program showed physical function improvement, compared with older adults that did not participate.…”
Section: Discussionmentioning
confidence: 98%
“…As the prevalence of obesity has increased rapidly worldwide [1], a sedentary lifestyle, one of the major causes of obesity and overweight, also has increased [2]. The amount of sedentary behavior during waking hours is especially high for office workers and students [3].…”
Section: Introductionmentioning
confidence: 99%